Presynaptically localized cyclic GMP-dependent protein kinase 1 is a key determinant of spinal synaptic potentiation and pain hypersensitivity - Luo, Ceng; Gangadharan, Vijayan; Bali, Kiran Kumar; Agarwal, Nitin; Kurejova, Martina; Tappe-Theodor, Anke; Kuner, Thomas; Kuner, Rohini (PLoS biology, 2012)
Electrophysiological and behavioral experiments in mice reveal that a cGMP-dependent kinase amplifies neurotransmitter release from peripheral pain sensors, potentiates spinal synapses, and leads to exaggerated pain.
Published March 13, 2012
Gesehen am 26.06.2018